Associative Response of Non-Legumes (Barley) and Legume (Peas) Grown in Different Proportions in Terms of Growth, Yield and Quality - Singh, Harbans (Journal of Soil and Water Conservation, 2022)
The growing of crops in association is an age old practice. It is by virtue of its manifold benefits, some of which being clearly understood by the farmers, such as insurance against pests and diseases, increased yield, reduced cost of cultivation, fulfilment of diverse needs, better utilization of space, manure and water, provision of balanced nutrition, soil and water conservation and its value in crop rotation. The system of mixed crop, so common in India, is undoubtedly a successful and profitable method which probably has done more to uphold the fertility of the Indian soils than any other practice (Mollison 1901).